Quality of life: commuter couples / Nor Habibah Tarmuji, Siti Noorul Ain Nor Azemi and Zulkifli Ab. Ghani Hilmi - Tarmuji, Nor Habibah; Nor Azemi, Siti Noorul Ain; Ab. Ghani Hilmi, Zulkifli (Research Management Institute (RMI), 2013)
Malaysia is indeed in a very comprehensive plan to ensure livelihood, poverty and social transformation. One of the strategies is to enhance the quality of life of Malaysians. Recently, commuter couples are becoming a phenomenon in Malaysia. Husbands and wives stay at different locations because of career commitment. According to the article in Utusan Malaysia dated 3rd March 2011, Jabatan Kemajuan Islam Malaysia (JAKIM) in 2009 recorded that a divorce occurred every 15 minutes. Thus, JAKIM has organized a lot of programs to overcome this problem. Besides that, there a lot of news on crimes, alcoholism and drug addiction among youth. Therefore, successful family is the most important factor to have quality future generations. The disruption of the family institution has a significant negative effect on children. Dual-career commuter couples also have risk, challenges the family upbringing and creates possibilities of disruption to the family. So, this study intends to determine the factors affecting the quality of life of commuter couples. Hopefully this study will be able to be a guideline in achieving a successful family life. The main purpose of this study is to determine which factor affects the quality of life of commuter couples such as physical, psychological, social, financial well-being, and child upbringing. Secondly it is to compare the quality of life of commuter couples according to some demographic factors. A simple random sampling will be used to select the number of respondents from a list of UiTM staff from the Department of Administration UiTM Pahang. The data will be collected using a combination of self-construct questionnaires and established questionnaire which is WHO Quality of Life-BREF (WHOQOL-BREF). Descriptive analysis, independent sample t-test, analysis of variance will be used to analyze the data. The result from this study is very important to improve the quality of life in terms of the physical, psychological, social, and financial well-being. Not only mothers but also fathers have an important contribution in their children's lives through the living arrangement for family members and the family structure.